A brief history of Business Ethics here and now - Gasparski, Wojciech W. (Annales. Etyka w Życiu Gospodarczym, 2019)
The article is a review of issues connected with business ethics and corporate social responsibility (CSR) in the last 20 years. Two decades have passed since the Sixth Polish Philosophical Congress took place in Toruń, where—for the first time in the history of Polish philosophical conventions—business ethics was recognized as a philosophical sub-discipline. It manifested itself in a special subsection of the Congress devoted to the topic, which was also kept at the next congress meetings. The paper is not a full review and most likely is not free from subjectivism. This is partly due to the fact that the subject matter falls within the scope of the philosophy of practicality—as the author interprets and refers to the philosophical system of Tadeusz Kotarbiński.